2014
DOI: 10.1098/rsbl.2014.0407
|View full text |Cite
|
Sign up to set email alerts
|

The cockroachBlattella germanicaobtains nitrogen from uric acid through a metabolic pathway shared with its bacterial endosymbiont

Abstract: Uric acid stored in the fat body of cockroaches is a nitrogen reservoir mobilized in times of scarcity. The discovery of urease in Blattabacterium cuenoti , the primary endosymbiont of cockroaches, suggests that the endosymbiont may participate in cockroach nitrogen economy. However, bacterial urease may only be one piece in the entire nitrogen recycling process from insect uric acid. Thus, in addition to the uricolytic pathway to urea, there must be glutamine synthetase assimilating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 21 publications
1
48
0
Order By: Relevance
“…; Patiño‐Navarrete et al. ). In our experiment, cockroaches were fed commercial rat chow, which contains relatively large amounts of crude P (~20%), during their juvenile development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Patiño‐Navarrete et al. ). In our experiment, cockroaches were fed commercial rat chow, which contains relatively large amounts of crude P (~20%), during their juvenile development.…”
Section: Discussionmentioning
confidence: 99%
“…First, this may represent an adaptation to maintain nutritional homeostasis in cockroaches. Most cockroach species, including N. cinerea (Kambhampati et al 2013), harbor endosymbiotic bacteria (Blattabacterium) within specialized cells in the fat body that enable them to store nitrogen as uric acid during times of excess P and recycle the nitrogen for amino acids when P is limited in the diet (Sabree et al 2009;Patiño-Navarrete et al 2014). In our experiment, cockroaches were fed commercial rat chow, which contains relatively large amounts of crude P (~20%), during their juvenile development.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient-providing symbionts are commonly found in hosts with restricted diets, for example, aphids feeding on phloem sap (Baumann, 2005), blood-feeding diptera (Wang et al, 2013) or grain weevils (Heddi et al, 1999). Symbionts can provide essential amino acids, vitamins or help in nitrogen recycling (Nakabachi et al, 2005;Feldhaar et al, 2007;Michalkova et al, 2014;Patino-Navarrete et al, 2014). Such bacteria are commonly harbored in bacteriocytes, specialized host cells that sometimes form special organ-like structures, the bacteriomes (Baumann, 2005) or are confined to the insect gut (Engel and Moran, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Patiño‐Navarrete et al . () demonstrated that in the cockroach Blattella germanica the nitrogen recycling pathway is chimeric, with participation of enzymes from the host and the bacterial symbiont B. cuenoti .…”
Section: Discussionmentioning
confidence: 99%